Landscape of transposable elements focusing on the B chromosome of the cichlid fish astatotilapia latifasciata - Coan, Rafael L. B. [UNESP]; Martins, Cesar [UNESP] (MDPI, 2018)
B chromosomes (Bs) are supernumerary elements found in many taxonomic groups. Most B chromosomes are rich in heterochromatin and composed of abundant repetitive sequences, especially transposable elements (TEs). B origin is generally linked to the A-chromosome complement (A). The first report of a B chromosome in African cichlids was in Astatotilapia latifasciata, which can harbor 0, 1, or 2 Bs Classical cytogenetic studies found high a TE content on this B chromosome. In this study, we aimed to understand TE composition and expression in the A. latifasciata genome and its relation to the B chromosome. We used bioinformatics analysis to explore the genomic organization of TEs and their composition on the B chromosome. The bioinformatics findings were validated by fluorescent in situ hybridization (FISH) and real-time PCR (qPCR). A. latifasciata has a TE content similar to that of other cichlid fishes and several expanded elements on its B chromosome. With RNA sequencing data (RNA-seq), we showed that all major TE classes are transcribed in the brain, muscle, and male and female gonads. An evaluation of TE transcription levels between B-and B+ individuals showed that few elements are differentially expressed between these groups and that the expanded B elements are not highly transcribed. Putative silencing mechanisms may act on the B chromosome of A. latifasciata to prevent the adverse consequences of repeat transcription and mobilization in the genome.
Keywords: Cytogenetics; Evolution; Extra chromosomes; Genomics; Repetitive elements; RNA-Seq; Supernumerary elements